2020
DOI: 10.1101/2020.06.21.20137000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health Condition and Test Availability as Predictors of Adults’ Mental Health during the COVID-19 Pandemic

Abstract: Background: Research identifying adults' mental health during the COVID-19 pandemic relies solely on demographic predictors without examining adults' health status during the COVID-19 pandemic as a potential predictor. Methods: An online survey of 669 adults in Malaysia was conducted during May 2-8, 2020, six weeks after a Movement Control Order (MCO) was issued. Findings: Adults' health condition had curvilinear relationships (horizontally reversed J-shaped) with insomnia, anxiety, depression and distress. R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…4); 50.0% (95% CI 41.8-58.2) for psychological distress (18 studies 39,47,52,59,63,65,70,72,78,79,85,86,88,102,110,118,121,128 , n = 81,815, Fig. 5); and 27.6% (95% CI 19.8-36.1) for sleep problems (15 studies 35,53,58,80,84,103,106,107,109,119,120,125,134,136,137 , n = 99,534, Fig. 6).…”
Section: Data Collectionmentioning
confidence: 99%
“…4); 50.0% (95% CI 41.8-58.2) for psychological distress (18 studies 39,47,52,59,63,65,70,72,78,79,85,86,88,102,110,118,121,128 , n = 81,815, Fig. 5); and 27.6% (95% CI 19.8-36.1) for sleep problems (15 studies 35,53,58,80,84,103,106,107,109,119,120,125,134,136,137 , n = 99,534, Fig. 6).…”
Section: Data Collectionmentioning
confidence: 99%
“…Introduction: COVID-19 pandemic has decreased the quality of life of individuals worldwide (Cal-Kayitmazbatir, 2021). It is reported that this epidemic caused various disorders such as distress, anxiety, depression, and insomnia in society (Choi et al, 2020;Dai et al, 2020;Kang et al, 2020). As a result, society's perception of health may change.…”
Section: Extended Abstractmentioning
confidence: 99%